2006
DOI: 10.1007/s00702-005-0429-7
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of serotonin transporters and its blockade by citalopram in patients with major depression using a novel SPECT ligand [123I]-ADAM

Abstract: We studied the midbrain SERT availability in patients with major depression and assessed the relation of SERT occupancy by citalopram to the treatment response. 21 non-medicated patients with major depression and 13 healthy controls were examined by [(123)I]-ADAM SPECT. The midbrain SERT availability (SERT V(3)'') was calculated using individual MRI scans. In 13/21 patients SPECT was repeated 7 days after oral medication with citalopram (10 mg/day). We found no significant difference in the mean midbrain SERT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 52 publications
5
39
1
1
Order By: Relevance
“…Our results confirm previous reports of similar SERT availability in the midbrain and diencephalon in MDD patients and healthy subjects [14][15][16][17][18]. Other studies have shown increased [19] or decreased [7][8][9][10][11][12][13] SERT availability in MDD patients compared with healthy subjects.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…Our results confirm previous reports of similar SERT availability in the midbrain and diencephalon in MDD patients and healthy subjects [14][15][16][17][18]. Other studies have shown increased [19] or decreased [7][8][9][10][11][12][13] SERT availability in MDD patients compared with healthy subjects.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
“…Studies comparing depressed patients with healthy subjects have shown decreased [7][8][9][10][11][12][13], unchanged [14][15][16][17][18] or increased [19] SERT availability in MDD patients. A negative correlation between SERT availability and the severity of depression, measured in terms of Hamilton depression rating scale (HDRS) scores, has been reported in patients with primary MDD [9] or Wilson's disease [20].…”
mentioning
confidence: 99%
“…Neuroimaging investigations, sampling subjects with early onset MDD who are medication free for greater than 2 months, are non-smoking and do not have comorbid axis I disorders, and also apply better quality radiotracer technology, tend to find either no change in regional 5-HTT binding or an increase in regional 5-HTT binding (Cannon et al 2007;Herold et al 2006;Ichimiya et al 2002;Meyer et al 2004a). Investigations which include sampling of subjects with late onset MDD, Correlations between dysfunctional attitudes (DAS) and serotonin transporter binding potential (5-HTT BP) in some of the larger regions in depressed subjects.…”
Section: Dysfunctional Attitudes During Major Depressive Episodes Andmentioning
confidence: 99%
“…A recent DATSCAN study has revealed moderately reduced abundance of dopamine transporters in striatum of never-treated patients with schizophrenia (Mateos et al 2007 ) , which seems somewhat at odds with the fi nding of increased effects of amphetamine, noted above. The [ (Frokjaer et al 2008 ) ; SPECT studies with this tracer have revealed increased serotonin transporters in the brainstem of subjects with borderline personality disorder (Koch et al 2007 ) , and have shown the occupancy at serotonin transporters in depressed patients under treatment with citalopram (Herold et al 2006 ) . SPECT tracers for serotonin receptors, as opposed to presynaptic serotonin transporters, are not yet widely available.…”
Section: The Radiation Physics Of Molecular Imagingmentioning
confidence: 98%